Structural relationship of the social-ecological and psychological constructs on the amount of physical activity among university's students in health campus, Universiti Sains Malaysia - Abdulrahman, Abdulwali Sabo (2019)
Introduction: Physical activity is affected by a network of interactions between social environmental factors (e.g., family and friends support), physical environmental factors (e.g., perceived availability and quality of exercise facilities), and psychological factors (e.g., psychological need satisfaction, self-efficacy, perceived benefits and barriers). Therefore, there is a need for scientific understanding of the inter-relationship between these variables in the context of physical activity behaviour. Objective: This study aimed to determine the measurement validity of the Malay translated version scales of social environment and physical environment. Subsequently, examine their structural relationship with psychological variables and amount of physical activity among undergraduate students in Health Campus, Universiti Sains Malaysia (USM). Method: The study was a cross-sectional design in nature, using a self-reported questionnaire among undergraduate students in Health Campus, USM. Participants were selected using the nonprobability method, a convenience sampling approach. Perceptions regarding social environment, physical environment, decisional balance, self-efficacy for exercise, psychological needs satisfaction in exercise, and amount of physical activity were assessed using Malay translated version scales. Descriptive statistics, confirmatory factor analysis (CFA), and structural equation modelling (SEM) were the employed statistical analyses. Results: A total of 422 students participated in this study. The mean age of the participants was 20.2 years (SD =1.27). The majority of the participants were female (69.7%) and Malay (81.3%). In the measurement model validity, the Malay version of social environment with 24 items revealed a good fit to the data with no item deleted: CFI = 0.931, TLI = 0.923, SRMR = 0.058, RMSEA (90%CI) = 0.060 (0.054, 0.066), RMSEA p-value = 0.002. The CR was 0.942 and 0.925, and the AVE was 0.593 and 0.542. The Malay translated version of the physical environment scale with five items also showed a good fit to the data with no item deleted: CFI = 0.989, TLI = 0.974, SRMR = 0.022, RMSEA = (90%CI) = 0.054 (0.00, 0.102), RMSEA p-value = 0.373. The CR was 0.743 and 0.627, and the AVE was 0.465 and 0.627. In addition, the SEM final model showed a good fit to the data: CFI = 0.968, SRMR = 0.036, RMSEA (90%CI) = 0.046 (0.025, 0.065), RMSEA p-value = 0.609 with eight hypotheses supported and three new pathways were added. Several indirect relationships were observed involving pathways from friends support, availability of exercise facilities, barriers and benefit of exercise, self-efficacy to physical activity. Conclusion: The final results provide psychometric evidence for using social environment and physical environment scales to evaluate perceived environmental factors that are associated with physical activity participation among university students in Malaysia. All items were retained and confirmed to be fit for the sample data. The hypothesised structural model tested in this study, supported some scientific evidence of direct and indirect relationships between social environmental and physical environmental variables with psychological variables (self-efficacy, decisional balance, and psychological needs satisfaction) and amount of reported physical activity. The findings can serve as a piece of valuable information that could help researchers, health policymakers, and health educators in understanding and promoting physical activity behaviours among university students.